2015
DOI: 10.1590/0100-3984.2014.0008
|View full text |Cite
|
Sign up to set email alerts
|

Value of renal cortical thickness as a predictor of renal function impairment in chronic renal disease patients

Abstract: ObjectiveTo determine the presence of linear relationship between renal cortical thickness, bipolar length, and parenchymal thickness in chronic kidney disease patients presenting with different estimated glomerular filtration rates (GFRs) and to assess the reproducibility of these measurements using ultrasonography.Materials and MethodsUltrasonography was performed in 54 chronic renal failure patients. The scans were performed by two independent and blinded radiologists. The estimated GFR was calculated using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
36
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 10 publications
7
36
1
2
Order By: Relevance
“…They also stated that the measurement of the thickness of the renal parenchyma, which is still widely used in the clinical practice to infer some chronic nephropathies should be discouraged, since it showed no statistical correlation with renal function impairment and therefore it is useless in this context. 6 Our present study further confirmed this finding.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…They also stated that the measurement of the thickness of the renal parenchyma, which is still widely used in the clinical practice to infer some chronic nephropathies should be discouraged, since it showed no statistical correlation with renal function impairment and therefore it is useless in this context. 6 Our present study further confirmed this finding.…”
Section: Discussionsupporting
confidence: 90%
“…The findings were closely consistent with those of Yamashita et al who found the mean cortical thickness to be 7.1 mm in their cases. 6 Beland et al reported a mean cortical thickness of 5.9 mm in CKD patients in their study. 17 Raised renal cortical echogenicity was reported in all the patients with CKD in this present study.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…To obtain renal measurements as a prognostic factor. Such measurements are important since in most cases CKD leads to a common final-stage condition characterized by small kidneys, cortical and parenchymal thinning (indicating atrophy) and hyperechogenicity indicating sclerosis and fibrosis (small, dense, echogenic kidneys); such findings indicate disease irreversibility and poor prognosis 6 .…”
Section: Introductionmentioning
confidence: 99%